Realization of red electroluminescence from Ga2O3:Eu/Si based light-emitting diodes - Huang, Yafei; Saito, Katsuhiko; Tanaka, Tooru; Guo, Qixin (Superlattices and microstructures, 2021)
Eu doped Ga2O3 film has been grown on n-Si (111) substrate by pulsed laser deposition. Excellent structural and optical properties of the obtained Ga2O3:Eu film have been confirmed by X-ray diffraction, Raman and photoluminescence measurements. Subsequently, Ga2O3:Eu/n-Si based light-emitting diode was successfully fabricated with a multilayer structure of ITO/Ga2O3:Eu/n-Si/Au. Intense red electroluminescence peaking at 615 nm has been observed at room temperature by naked eyes from the fabricated device when a positive bias voltage is applied on the n-Si substrate. The current-voltage characteristics and electroluminescence spectra indicate that the Ga2O3:Eu/n-Si based light-emitting diode has a rather low driven voltage of ~7.9 V. The origin of the Eu-related electroluminescence has been clarified to originate from the defect-assisted energy transfer from Ga2O3 host to Eu3+ ions. We believe that this study will offer the possibility to develop the silicon-compatible full-color displays or lighting technology using Ga2O3 as host material. •Eu doped β-Ga2O3 film was deposited on n-Si substrate by pulsed laser deposition.•Red light-emitting diode was fabricated based on Ga2O3:Eu/n-Si heterostructure.•Intense red electroluminescence at 615 nm was achieved from the diode with a low driven voltage of 7.9 V.•The electroluminescence mechanism of Ga2O3:Eu/n-Si based diode was investigated.